Immune cell landscape and immunotherapy of medulloblastoma - Jin Zhang; Tianyou Wang (Wiley, 2021)
ABSTRACT Medulloblastoma is the most common primary pediatric malignancy of the central nervous system. Recurrent and refractory patients account for approximately 30% of them. Immune cells are an important component of the brain tumor microenvironment, including tumor‐associated macrophages, T lymphocytes, natural killer cells, dendritic cells, neutrophils and B lymphocytes. Understanding how they behave and interact is important in the investigation of the onset and progression of medulloblastoma. Here, we overview the features and recent advances of each component of immune cells in medulloblastoma. Meanwhile, immunotherapy is a promising but also challenging treatment strategy for medulloblastoma. At present, there are a growing number of immunotherapeutic approaches under investigation including immune checkpoint inhibitors, oncolytic viruses, cancer vaccines, chimeric antigen receptor T cell therapies, and natural killer cells in recurrent and refractory medulloblastoma patients.